Penyuluhan Pentingnya Mengkonsumsi Buah dan Sayur untuk Menjaga Imunitas Tubuh - Sari, Rumania Astika (Universitas Katolik Soegijapranata, 2024)
Iron nutrition occurs in children who only like milk without eating anything else such as side dishes, rice, vegetables and fruit. Milk does not contain iron, so it must be supplemented with the main food, namely vegetables, and do not follow the child's wishes regarding food. Mothers have to make sure their children don't become picky eaters. From fruits and vegetables the child can get all the nutritional food in its entirety. Children also get the opportunity to taste fruit and vegetables as old as they taste. So eating fruits and vegetables is actually much healthier, and also very beneficial. The purpose of conducting this research is to find out the factors associated with consuming fruits and vegetables in early childhood. The purpose of this study was also to find out the relationship between parents' education, parents' occupation, parents' knowledge about vegetables, and attitudes and behavior of parents towards children who consume fruits and vegetables. Through this fruit and vegetable education activity, it is hoped that the community, especially children, will have more insight into the importance of consuming fruits and vegetables. The research method is based on the problems to be examined, so this research is included in the type of quantitative research with a descriptive quantitative approach. The population is all the characteristics that are the object of research, where these characteristics relate to all groups of people who are the center of attention for researchers. The results of this study were that some of the participants attended elementary school (100%) with male (17%) and female (83%) genders. The results of community service found that 30 children, all (100%). The results of the Pre-Sceneaning are with Percentage (100%), and the Results of Post-Sceneing with low (7%), high (93%) Percentage results.